2022
DOI: 10.1039/d2cy00845a
|View full text |Cite
|
Sign up to set email alerts
|

Recent development towards alkene hydroformylation catalysts integrating traditional homo- and heterogeneous catalysis

Abstract: Hydroformylation of alkenes, the most important homogenously catalyzed industrial process, has been widely used into the manufacture of aldehydes, and the resulting aldehydes are further converted into high value-added alcohols,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 168 publications
0
11
0
Order By: Relevance
“…Heterogeneous hydroformylation has attracted much attention due to the difficult separation of catalysts and products in homogeneous processes. , The hydroformylation reaction converts alkenes and syngas (CO/H 2 ) into corresponding aldehydes, where Rh δ+ is usually considered as the main active site. , Rhodium phosphides Rh 2 P were reported to exhibit high activity in ethylene, styrene, and 1-hexene hydroformylation reactions, which was attributed to the electronic modification of Rh sites by inorganic phosphorus in MPs (Figure A ). The X-ray photoelectron spectroscopy (XPS) and X-ray absorption near-edge structure (XANES) results demonstrated that Rh was positively charged between Rh(0) and Rh­(III) in Rh 2 P .…”
Section: Electronic Effects: Electron Withdrawingmentioning
confidence: 99%
“…Heterogeneous hydroformylation has attracted much attention due to the difficult separation of catalysts and products in homogeneous processes. , The hydroformylation reaction converts alkenes and syngas (CO/H 2 ) into corresponding aldehydes, where Rh δ+ is usually considered as the main active site. , Rhodium phosphides Rh 2 P were reported to exhibit high activity in ethylene, styrene, and 1-hexene hydroformylation reactions, which was attributed to the electronic modification of Rh sites by inorganic phosphorus in MPs (Figure A ). The X-ray photoelectron spectroscopy (XPS) and X-ray absorption near-edge structure (XANES) results demonstrated that Rh was positively charged between Rh(0) and Rh­(III) in Rh 2 P .…”
Section: Electronic Effects: Electron Withdrawingmentioning
confidence: 99%
“…Therefore, the separation and recovery of both Rh/ligands and acid catalysts is an important issue to be considered when designing heterogeneous catalysts. As a kind of emerging support, the porous organic polymers (POPs) containing phosphorus ligands have been successfully used in the heterogeneous hydroformylation reaction owing to the high specific surface area and rich modifiability of phosphorus ligand moieties. In addition, because of their outstanding stability, high adsorption capacity, confinement effects, and high surface areas, molecular sieves have been widely used in organic reactions as a solid acid catalyst. , Herein, based on the advantages of the two materials, we developed a composite catalyst consisting of Rh/POP-BINAPa&PPh 3 and ZSM-35(10) for the heterogeneous one-pot hydroformylation–acetalization of olefins (Scheme ). In the solid carrier, the BINAPa ligand with the strong π-acidity was used to achieve a highly reactive and selective hydroformylation process, and PPh 3 monomers could construct the porous framework with a high specific surface area, improving the stability and the loading capacity of Rh ion. , Compared with the previously reported heterogeneous catalyst, the composite catalyst of Rh/POP-BINAPa&PPh 3 @ZSM-35­(10) showed higher excellent activities (turnover number, TON up to 10,000) and regioselectivities ( l / b = 30.2–87.9).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their excellent activity and selectivity, traditional homogeneous rhodium catalysts are not easily recyclable and not sufficiently stable. Efforts have been made to immobilize rhodium complexes onto solid supports for easy separation, in which Rh species are still coordinated with organic ligands [3][4][5][6]. Alternatively, a phosphine ligand can be added in the postsynthesis stage to modulate Rh species on solid supports owing to its firm metal-ligand coordination [7].…”
Section: Introductionmentioning
confidence: 99%